2010
DOI: 10.2135/cropsci2009.06.0355
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Wild Yellow Lupin from Northwestern Spain

Abstract: Wild yellow lupin (Lupinus luteus L.) is one of the three species of the genus Lupinus that grows naturally in Galicia (northwestern Spain). In this dairy region imported lupin is widely used as a cheap plant‐derived protein for livestock feed. Our objectives were to investigate variation in yellow lupin accessions from northwestern Spain, determine the relationships among them, and identify useful accessions for production and breeding. Fifty wild accessions and one Portuguese landrace were evaluated for 21 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 12 publications
1
7
1
Order By: Relevance
“…hispanicus populations have a height average of 73.9 cms and they produce 159 g of green biomass and 14.2 g of dry biomass (Table 2). These parameters are lower than that found in a collection of yellow lupin (L. luteus) population of northwestern Spain (Lema and Lindner 2010), with an average of 91.6 cm and 194 and 19.1 g of green and dry biomass, respectively.…”
Section: Description Of the Collectioncontrasting
confidence: 70%
See 3 more Smart Citations
“…hispanicus populations have a height average of 73.9 cms and they produce 159 g of green biomass and 14.2 g of dry biomass (Table 2). These parameters are lower than that found in a collection of yellow lupin (L. luteus) population of northwestern Spain (Lema and Lindner 2010), with an average of 91.6 cm and 194 and 19.1 g of green and dry biomass, respectively.…”
Section: Description Of the Collectioncontrasting
confidence: 70%
“…Arrieta et al (1993) found an average of 211 days to first flower in L. hispanicus populations from west central of Spain and Cowling et al (1998) did not find early flowering types in this species. The growing cycle of L. hispanicus is similar to that of yellow lupin (L. luteus) collected in the same region and characterized by Lema and Lindner (2010). High vernalization requirements and small and impermeable seeds maybe the cause of late flowering and maturity of the accessions.…”
Section: Description Of the Collectionmentioning
confidence: 76%
See 2 more Smart Citations
“…Arrieta et al (1993) found an average of 211 days to first flower in L. hispanicus populations from west central of Spain and Cowling et al (1998) did not find early flowering types in this species. The growing cycle of L. hispanicus is similar to that of yellow lupin (L. luteus) collected in the same region and characterized by Lema and Lindner (2010). High vernalization requirements and small and impermeable seeds maybe the cause of late flowering and maturity of the accessions.…”
Section: Description Of the Collectionmentioning
confidence: 76%